PENGARUH SERVICE FAILURE SEVERITY TERHADAP KEPUASAN, KEPERCAYAAN, KOMITMEN DAN NEGATIF WORD OF MOUTH - Linda Desafitri RB (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
The background of this research was to investigate the main and interactive effects of the severity of the service failure, specifically investigate the main effect of service failure severity on satisfaction,trust, commitment, and negative word of mouth. This investigation of the role of the severityconstruct will aid researchers and managers in better understanding and managing the service recovery process under different conditions.The objectives of this research is to extends previous research by investigating the role of service failure severity within the existing framework of customer’s post-recovery evaluation and their future relationship with a service provider.The design of this research applies a survey toward unit analysis on customer Auto2000 Jakarta, which involved 142 respondent.the number of sample being respondent in this research. Meanwhile, the required data consist of five variables : service failure severity, satisfaction, trust, commitmentand negative word of mouth.The result of the study concludes that service failure severity has a significant main effect on satisfaction with service recovery. Despite the positif influence of a strong recovery on satisfaction,there remained a negatif influence on satisfaction as a result of a more severe servicefailure. In addition , the severity of a service failure also had a main effect on customer trust, commitment and the likelihood of engaging in negative word of mouth after the service failure.Keywords : Service failure severity, satisfaction, trust, commitment and negative word of mouth